Distinguishing between anomalous origin of the left coronary artery from the pulmonary trunk and dilated cardiomyopathy: role of echocardiographic measurement of the right coronary artery diameter. Issue 2 (February 1989) - Koike, K; Musewe, N N; Smallhorn, J F; Freedom, R M
Abstract : Patients with anomalous origin of the left coronary artery from the pulmonary trunk usually have a large right coronary artery. This study examines the diagnostic value of measuring the diameter of the right coronary artery by echocardiography in distinguishing between this lesion and other causes of dilated cardiomyopathy. The diameter of the right coronary artery and the right coronary artery/aorta ratio were measured in the parasternal short axis view in 40 controls, 11 patients with dilated cardiomyopathy, and 10 with anomalous origin of the left coronary artery from the pulmonary trunk. In the controls, the diameter of the right coronary artery increased with age, but the right coronary artery/aorta ratio remained constant. In the control group the 95% upper limits of prediction for right coronary artery diameter were 1.6 mm for one month of age, 1.8 mm for three months, 2.0 mm for one year, 2.2 mm for two years, 2.4 mm for three years, 2.6 mm for four years, 2.7 mm for six years, 3.0 mm for eight years, and 3.2 mm for 10 years; and for right coronary/aorta ratios the limits were 0.17 for one month to one year, 0.18 for one to six years, 0.19 for six to 10 years, and 0.20 for more than 10 years. All patients with dilated cardiomyopathy had normal right coronary artery diameters and right coronary artery/aorta ratios (0.10-0.13). Those patients with anomalous origin of the left coronary artery from the pulmonary trunk had larger than normal right coronary artery diameter and a significant increase in the right coronary artery/aorta ratio (0.21-0.29). The presence of an anomalous left coronary artery was likely if the diameter of the right coronary artery or the right coronary artery/aorta ratio was larger than the normal 95% limits of prediction.